Fiberoptic Bronchoscopic Findings in Patients Suffering from Emerging Pulmonary Lophomoniasis: A First Registry-Based Clinical Study - Aliyali, Masoud; Taheri, Amirmasoud; Fakhar, Mahdi; Sharifpour, Ali; Nakhaei, Maryam; Abedi, Siavash; Mehravaran, Hossein; Safanavaei, Sepideh (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. Lophomonas blattarum is an emerging protozoan agent that mainly infects the lower respiratory system, causing pulmonary lophomoniasis. The bronchoscopic findings in patients with pulmonary lophomoniasis have not been investigated yet. Accordingly, we assess the bronchoscopic findings of lophomoniasis in patients suffering from pulmonary lophomoniasis through a registry-based clinical study. Methods. In this retrospective study, of 480 patient candidates for bronchoscopy, 50 Lophomonas-positive patients were enrolled. Demographic data, relevant characteristics, and bronchoscopy findings of the patients were recorded and analyzed. Results. Overall, 50 (male = 32, female = 18) patients with an average age of 61.8 ± 13.3 years were examined. Nineteen patients (38%) had normal bronchoscopic findings, and 31 patients (62%) had abnormal bronchoscopic findings. According to the severity index, most (52%) of patients had mild severity, followed by moderate (30%) and severe (18%) cases. The highest involvement was in the right lung bronchus (46%), and the lowest was in the carina (8%). Furthermore, purulent and mucosal secretions in the right and left lung bronchus were the most abnormalities found in different anatomical locations. Conclusion. For the first time, the current study demonstrated that pulmonary lophomoniasis does not have pathognomonic bronchoscopic findings. However, each suspected patient must be checked for lophomoniasis, even with normal bronchoscopic findings, particularly in endemic areas.